Accuracy of whole-body MRI in the assessment of splenic involvement in lymphoma. (February 2016) - Littooij, Annemieke S; Kwee, Thomas C; Barber, Ignasi; Granata, Claudio; de Keizer, Bart; Beek, Frederik JA; Hobbelink, Monique G; Fijnheer, Rob; Stoker, Jaap; Nievelstein, Rutger AJ
Background: Accurate evaluation of the spleen is an important component of staging lymphoma, because this may have prognostic and therapeutic implications. Purpose: To determine the diagnostic value of whole-body magnetic resonance imaging (MRI), including diffusion-weighted imaging (whole-body MRI-DWI) in the detection of splenic involvement in lymphoma. Material and Methods: This IRB approved, prospective multicenter study included a total of 107 patients with newly diagnosed, histologically proven lymphoma who underwent 1.5 T whole-body MRI-DWI and FDG-PET/CT. Whole-body MRI-DWI and FDG-PET/CT were independently evaluated by a radiologist and a nuclear medicine physician, in a blinded manner. Splenic involvement at MRI was defined as splenic index > 725 cm 3 or discrete nodules. At FDG-PET/CT splenic involvement was defined as splenic uptake greater than liver uptake or hypodense nodules at contrast-enhanced CT. FDG-PET/CT augmented with follow-up imaging after treatment was used as reference standard. Results: Splenic involvement was detected with FDG-PET/CT in 21 patients, all demonstrating response to treatment. The sensitivity, specificity, positive predictive value, and negative predictive value of whole-body MRI-DWI for the detection of splenic involvement were 85.7 %, 96.5 %, 85.7%, and 96.5%, respectively. Three out of six discrepancies were related to suboptimal criterion of splenic size used with whole-body MRI-DWI versus the size-independent FDG uptake. Conclusion: Whole-body MRI-DWI is reasonably accurate in the detection of splenic lymphomatous involvement.